2017
DOI: 10.1111/ane.12883
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive perampanel in partial-onset seizures: Asia-Pacific, randomized phase III study

Abstract: Adjunctive perampanel (8 and 12 mg/d) significantly improved seizure control in patients with refractory POS. Safety and tolerability were acceptable at daily doses of perampanel 4-12 mg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
120
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(147 citation statements)
references
References 17 publications
17
120
1
Order By: Relevance
“…The phase‐3 multicenter, randomized, double‐blind, placebo‐controlled studies 304 (ClinicalTrials.gov identifier NCT00699972), 305 (NCT00699582), 306 (NCT00700310), and 335 (NCT01618695) were undertaken to assess the efficacy and safety of adjunctive once‐daily perampanel in patients with focal seizures with or without FBTC seizures. Briefly, studies 304, 305, and 306 were conducted in more than 40 countries on 6 continents, and study 335 was conducted in Japan, China, South Korea, Australia, Thailand, Malaysia, and Taiwan.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The phase‐3 multicenter, randomized, double‐blind, placebo‐controlled studies 304 (ClinicalTrials.gov identifier NCT00699972), 305 (NCT00699582), 306 (NCT00700310), and 335 (NCT01618695) were undertaken to assess the efficacy and safety of adjunctive once‐daily perampanel in patients with focal seizures with or without FBTC seizures. Briefly, studies 304, 305, and 306 were conducted in more than 40 countries on 6 continents, and study 335 was conducted in Japan, China, South Korea, Australia, Thailand, Malaysia, and Taiwan.…”
Section: Methodsmentioning
confidence: 99%
“…Perampanel is also indicated for monotherapy use for focal seizures in the United States . Phase‐3 studies have shown that adjunctive perampanel significantly improved seizure control in patients with treatment‐resistant focal seizures with or without focal to bilateral tonic‐clonic (FBTC) seizures (previously referred to as secondarily generalized seizures) …”
Section: Introductionmentioning
confidence: 99%
“…The designs of studies 307 and 335 have been reported previously . Briefly, in study 307, patients recruited from Africa, Asia, Latin America, Europe, North America, and Australia were aged ≥12 years, had focal seizures with or without FBTC seizures despite taking one to 3 concomitant antiepileptic drugs at baseline, and had completed one of the perampanel phase 3 trials (studies 304, 305, or 306) .…”
Section: Methodsmentioning
confidence: 99%
“…Asian patients were among the global population enrolled in the phase 3 clinical trials and extension study . To specifically assess the efficacy and safety of perampanel as adjunctive therapy in patients aged ≥12 years with refractory focal seizures with or without FBTC seizures from Asia, a randomized, double‐blind, placebo‐controlled trial (study 335; NCT01618695) was conducted, which included an extension phase . At the end of the double‐blind phase of study 335, perampanel demonstrated a statistically significant change in seizure frequency per 28 days from baseline at doses of 8 mg (−29.0%; P = 0.0003) and 12 mg (−38.0%; P < 0.0001) compared with placebo .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation